2012
DOI: 10.1007/s11064-012-0737-x
|View full text |Cite
|
Sign up to set email alerts
|

The Interactions of Nitric Oxide and Acetylcholine on Penicillin-Induced Epilepsy in Rats

Abstract: The aim of this study was to investigate the interaction between nitric oxide (NO) and acetylcholine (ACh) in penicillin-induced experimental epilepsy. Adult male Wistar rats weighing 220 ± 35 g were used in the experiments. The epileptiform activity was induced by microinjection of penicillin (200 IU/1 μl) into the left sensorymotor cortex. Electrocorticogram was recorded by using Ag/AgCl ball electrodes. Sodium nitroprusside (SNP), a NO donor, given intracortically 30 min after penicillin significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
1
0
2
Order By: Relevance
“…Gasotransmitters such as nitric oxide (NO) and hydrogen sulfide (H 2 S) are endogenously produced gas molecules which induce unique signaling responses in cellular system. Extensive studies revealed that the gasotransmitters are associated with a variety of physiological and pathological process. Nitric oxide, produced by l -arginine with the enzymic reaction of nitric oxide synthase (NOS), is a multifunctional signal molecule and a ubiquitous signaling molecule regulating vascular tone, neuronal, tumor progression, and immunology. Meanwhile, hydrogen sulfide (H 2 S), historically known as a toxic pollutant, has recently been recognized for its regulatory roles in the cardiovascular, nervous, and immune systems. The pivotal functions of NO and H 2 S in various biological phenomena have been individually been identified. Recent research has increasingly revealed the cardiovascular similarities between H 2 S and NO, including their ability to stimulate angiogenesis, relax vascular smooth muscle, and protect against ischemia-reperfusion injury in the heart. The relationship of these two gasotransmitters suggests that exploring their interactions in biological systems using reliable and effective molecular tools would be of significant interest in elucidating both physiological and pathological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Gasotransmitters such as nitric oxide (NO) and hydrogen sulfide (H 2 S) are endogenously produced gas molecules which induce unique signaling responses in cellular system. Extensive studies revealed that the gasotransmitters are associated with a variety of physiological and pathological process. Nitric oxide, produced by l -arginine with the enzymic reaction of nitric oxide synthase (NOS), is a multifunctional signal molecule and a ubiquitous signaling molecule regulating vascular tone, neuronal, tumor progression, and immunology. Meanwhile, hydrogen sulfide (H 2 S), historically known as a toxic pollutant, has recently been recognized for its regulatory roles in the cardiovascular, nervous, and immune systems. The pivotal functions of NO and H 2 S in various biological phenomena have been individually been identified. Recent research has increasingly revealed the cardiovascular similarities between H 2 S and NO, including their ability to stimulate angiogenesis, relax vascular smooth muscle, and protect against ischemia-reperfusion injury in the heart. The relationship of these two gasotransmitters suggests that exploring their interactions in biological systems using reliable and effective molecular tools would be of significant interest in elucidating both physiological and pathological mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…protetor de NPS para as crises epilépticas. Corroborando com os nossos resultados o estudo de Marangoz e colaboradores(Marangoz et al, 2012) sobre crises epilépticas induzidas por penicilina (200iU/1µL) em ratos tratados com acetilcolina (ACh) e NPS mostrou redução nos disparos neuronais de frequência para crises mesmo a ACh aumentando a atividade epileptiforme dentro 5 minutos após 30 minutos da administração de penicilina. Quando ACh e NPS foram administrados juntos, a frequência de disparos neuronais da atividade epileptiforme foi suprimida.…”
unclassified
“…Quando a ACh foi administrada sozinha, houve facilitação da atividade epileptiforme, e com NPS aumentou os efeitos anticonvulsivos. Os mecanismos de maior supressão ACh+NPS em atividade epileptiforme induzido por penicilina ainda não são conhecidos, mas podem serMarangoz et al, 2012). Todavia de acordo com McCarthy e colaboradores (1965) a QUET também poderia ter efeitos anticonvulsivantes em modelos de epilepsia gerados elétrico ou quimicamente.…”
unclassified